Paternal experiences of their children’s diagnosis of Cystic Fibrosis following newborn screening diagnosis - Priddis, Lynn; Dunwoodie, Jane; Balding, E.; Barrett, A.; Douglas, T. (Cambridge Publishing, 2010)
Background: Fathers are a neglected group in parenting research, yet they have significant influence on family systems. This paper reports on the experiences of a group of fathers as they manage the impact on the family of the chronic medical challenge of Cystic Fibrosis (CF) in their child.Method: Fifteen fathers of children diagnosed with CF under the newborn screening (NBS) procedures in Western Australia (WA) participated in semi-structured interviews. The transcribed interviews were analysed for common themes using qualitative content analysis, following established procedures for process and rigour. Results: Receipt of a diagnosis of CF for a child altered relationships within the family system. Fathers in this study mostly used internalised and pragmatic coping strategies to assist them to manage anxiety and to come to terms with their child’s diagnosis. These strategies allowed these fathers to shift their focus from the crisis of diagnosis to the functioning of their family. Conclusions: Fathers play an important protective role in families, often so well that their own needs for support are overlooked. Clinical implications are discussed.